Indonesian Framework for Nurse-Patient Therapeutic Relationships: Insights From Cancer Ward Experiences - Venthy Wullur, Novita; Lamonge, Annastasia Sintia; Versoza, Catherine; Sumilat, Vervando (Jurnal Kesehatan Manarang, 2025)
Cancer care requires exceptional therapeutic relationships due to patients' complex physical and emotional needs, yet these relationships face unique challenges in resource-constrained settings. In Indonesian oncology units, where high patient volumes and limited resources strain nurse-patient interactions, understanding the current state of therapeutic relationships becomes particularly crucial.  This study aims to explore the nurse-patient therapeutic relationship along with respect, genuineness, empathy, trust, and confidentiality, to identify problems and challenges encountered by nurses and patients related to their therapeutic relationship, and to develop a proposed nurse-patient therapeutic framework for cancer patients in Indonesian contexts. A descriptive phenomenology approach was used in this study. 17 nurses and 15 patients were recruited  using a purposive sampling method. Data was collected through in-depth interviews, verbatim transcribed, and thematically analyzed. Total 11 themes and 24 sub-themes emerged in 5 aspects of the nurse-patient therapeutic relationship. Problems and challenges encountered by nurses and patients need to be solved by improving nurse communication and developing a trusting relationship with patients and improving patients’ comfort through improving hospital facilities. The proposed framework of the nurse-patient therapeutic relationship between nurses and patients may be used as the basis for developing a standard of nursing care for cancer patients.